2022
DOI: 10.1111/aor.14431
|View full text |Cite
|
Sign up to set email alerts
|

Generation of glucose sensitive insulin‐secreting cells from human induced pluripotent stem cells on optimized polyethersulfone hybrid nanofibrous scaffold

Abstract: Background: In the realm of diabetes treatment, various strategies have been tried, including islet transplantation and common drug therapies, but the limitations of these procedures and lack of responsive to the high number of patients have prompted researchers to develop a new method. In recent decades, the use of stem cells and three-dimonsional (3D) scaffold to produce insulin-secreting cells is one of the most promising new approaches. Meanwhile, human-induced pluripotent stem cells (iPSCs) propose due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…For example, Hosseini et al constructed silk/PES hybrid nanofibers to mimic the in vivo microenvironment for human adipose-derived stem cell differentiation into insulin-producing cells (IPCs). 135 Ahmadi et al found that the differentiated cells on 3D silk/PES nanofibers scaffold expressed pancreatic specific-markers such as insulin and pdx1 at higher levels than that on tissue culture plates, 136 demonstrating the advantages of composite nanofibers for IPSC-derived insulin-producing cell proliferation. Similarly, Ghollasi et al grafted laminin on the PES nanofibers to investigate the neural differentiation of human-induced pluripotent stem cells (hiPSCs).…”
Section: Applications In Biomedical Engineeringmentioning
confidence: 99%
“…For example, Hosseini et al constructed silk/PES hybrid nanofibers to mimic the in vivo microenvironment for human adipose-derived stem cell differentiation into insulin-producing cells (IPCs). 135 Ahmadi et al found that the differentiated cells on 3D silk/PES nanofibers scaffold expressed pancreatic specific-markers such as insulin and pdx1 at higher levels than that on tissue culture plates, 136 demonstrating the advantages of composite nanofibers for IPSC-derived insulin-producing cell proliferation. Similarly, Ghollasi et al grafted laminin on the PES nanofibers to investigate the neural differentiation of human-induced pluripotent stem cells (hiPSCs).…”
Section: Applications In Biomedical Engineeringmentioning
confidence: 99%